Case Report: Novel Monitoring for Anaerobic Conditions Detected by Respiratory Quotient in a Critically Ill Pediatric Patient - Hayashi, Kenichiro; Matsui, Hikoro (Frontiers in Pediatrics, 2022)
Background: Hyperlactemia after cardiopulmonary bypass is associated with adverse events during the early postoperative period in children. Lactate levels are affected by the balance between production and clearance and may lag behind the anaerobic response. Here, we report a neonatal case under anaerobic conditions after cardiac surgery, whose expired gas parameters dramatically changed before a rise in blood lactate. Case presentation: A 23-day-old girl with tetralogy of Fallot was admitted to the pediatric intensive care unit after modified Blalock-Taussig shunt operation. As hemoconcentration increased and pleural fluid and ascites accumulated, we performed partial exchange transfusion (PExT) to prevent shunt occlusion. Ten minutes after PExT, oxygen uptake and carbon dioxide production suddenly dropped, while the respiratory quotient began to rise steeply before hyperlactatemia developed a few hours later. Conclusion: Analysis of expired gas in critically ill children can detect the transition from aerobic to anaerobic conditions before hyperlactatemia.